Dynamic network biomarker analysis discovers IbNAC083 in the initiation and regulation of sweet potato root tuberization. (20th September 2021) - He, Shutao; Wang, Hongxia; Hao, Xiaomeng; Wu, Yinliang; Bian, Xiaofeng; Yin, Minhao; Zhang, Yandi; Fan, Weijuan; Dai, Hao; Yuan, Ling; Zhang, Peng; Chen, Luonan
SUMMARY: The initiation and development of storage roots (SRs) are intricately regulated by a transcriptional regulatory network. One key challenge is to accurately pinpoint the tipping point during the transition from pre‐swelling to SRs and to identify the core regulators governing such a critical transition. To solve this problem, we performed a dynamic network biomarker (DNB) analysis of transcriptomic dynamics during root development in Ipomoea batatas (sweet potato). First, our analysis identified stage‐specific expression patterns for a significant proportion (>9%) of the sweet potato genes and unraveled the chronology of events that happen at the early and later stages of root development. Then, the results showed that different root developmental stages can be depicted by co‐expressed modules of sweet potato genes. Moreover, we identified the key components and transcriptional regulatory network that determine root development. Furthermore, through DNB analysis an early stage, with a root diameter of 3.5 mm, was identified as the critical period of SR swelling initiation, which is consistent with morphological and metabolic changes. In particular, we identified a NAM/ATAF/CUC (NAC) domain transcription factor, IbNAC083, as a core regulator of this initiation in the DNB‐associated network. Further analyses and experiments showed that IbNAC083, along with its associated differentially expressed genes, induced dysfunction of metabolism processes, including the biosynthesis of lignin, flavonol and starch, thus leading to the transition to swelling roots. Significance Statement: The initiation and development of storage roots (SRs) are intricately regulated by a complex regulatory network, and most studies just focus on static molecular biomarkers. In this study, based on our gene expression profiles of sweet potato roots at different developmental stages, we studied the molecular mechanisms of SR development from the perspectives of dynamics and network, and identified the tipping point and key regulators of the SR swelling process by the dynamic network biomarker method.